Drivers’ visual search behavior toward vulnerable road users at junctions as a function of cycling experience - Robbins, Chloe J.; Chapman, Peter (Sage, 2018)
Objective The current study investigated the behaviour and visual attention of two groups of drivers with differing pedal cycling experience (pedal cyclists and non-pedal cyclists), towards vulnerable road users at junctions in a driving simulator. Background Pedal cyclists and motorcyclists are involved in a disproportionate number of crashes given the distance they travel, with a high proportion of these crashes occurring at junctions. Many studies have found that car drivers who also hold a motorcycle licence have increased awareness towards motorcycles. Method The task involved approaching a T-junction and turning right when it was deemed to be safe. In Study 1 the junction was controlled by a give way sign, and in Study 2 the junction was controlled by a stop sign. Each T-junction contained a target vehicle (car, motorcycle or pedal cycle), approaching from a near, medium or far distance from the junction. Results Participants did not look at pedal cycles approaching from a far distance for as long as they looked at approaching motorcycles and cars, despite all vehicles travelling at identical speeds. No differences were found between pedal cyclists and non-pedal cyclists on any visual attention measures, indicating that pedal cycling experience was not associated with differences in drivers’ attention towards pedal cycles. Conclusions Findings have implications for road safety, demonstrating subtle differences in drivers’ every day visual attention towards differing vehicle types. Application This research has the potential to inform the development of in-car technical assistive systems, improving the safety of vulnerable road users at junctions.